Questions of Mediation in the Translation of Tourist Texts (Altre Modernità, 2012)
The notion of “mediation”  - meant as a symbolic space for interplay and negotiation -  is one on the main characteristic of the language of tourism. The force of tourism communication lies in its capacity to develop a language capable of coping with the functions and needs of the extremely diverse components of this field. Hence, a variety of discursive strategies and linguistic features are exploited and textually organised into hybrid text genres, in order to meet the needs of professionals working in several areas (transport, tourist information, tourist accommodation etc). Not only is tourism communication subject to a high degree of negotiation at textual level, but the concept of “mediation” surfaces also at the ideational level of language. The purpose of tourism is to negotiate the encounter with the Other, and in doing so identities are very often re-arranged and distorted. The object of this paper is to analyse what happens when tourism-fashioned identities are transported across linguistic, social and cultural barriers.